Investigation of Pineapple (Ananas Comosus) Wine Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Pineapple is a wonderful tropical fruit having exceptional juiciness, vibrant tropical flavor and immense health benefits. Pineapples are consumed as fresh, cooked, juiced, and fermented in a wide array of food stuffs. This fruit is highly perishable and seasonal.  Therefore we explored a wine fermentation from pineapple by focusing on the effect of different parameters such as Pectinex Ultra SP-L concentration and time of treatment for juice extraction, yeast inculate for wine fermentation, and secondary fermentation to wine quality. Our results proved that 0.4% Pectinex Ultra SP-L was used for juice extraction, 0.75% sacchromyces cerevisiae was used for the main fermentation at 11.5oC, and 3 weeks of sencondary fermentation in dark bottle at 9.5oC was applied to get a pleasant pineapple quality.Keywords: Pineapple, Wine, Fermentation, Sacchromyces cerevisiae, Pectinex Ultra SP-L.